Early suboptimal ART adherence was associated with missed clinical visits in HIV-infected patients in Asia. Issue 12 (2nd December 2018) - Jiamsakul, Awachana; Kerr, Stephen J.; Kiertiburanakul, Sasisopin; Azwa, Iskandar; Zhang, Fujie; Chaiwarith, Romanee; Wong, Wingwai; Ly, Penh Sun; Kumarasamy, Nagalingeswaran; Ditangco, Rossana; Pujari, Sanjay; Yunihastuti, Evy; et al.
ABSTRACT: Missed clinic visits can lead to poorer treatment outcomes in HIV-infected patients. Suboptimal antiretroviral therapy (ART) adherence has been linked to subsequent missed visits. Knowing the determinants of missed visits in Asian patients will allow for appropriate counselling and intervention strategies to ensure continuous engagement in care. A missed visit was defined as having no assessments within six months. Repeated measures logistic regression was used to analyse factors associated with missed visits. A total of 7100 patients were included from 12 countries in Asia with 2676 (37.7%) having at least one missed visit. Patients with early suboptimal self-reported adherence <95% were more likely to have a missed visit compared to those with adherence ≥95% (OR = 2.55, 95% CI(1.81–3.61)). Other factors associated with having a missed visit were homosexual (OR = 1.45, 95%CI(1.27–1.66)) and other modes of HIV exposure (OR = 1.48, 95%CI(1.27–1.74)) compared to heterosexual exposure; using PI-based (OR = 1.33, 95%CI(1.15–1.53) and other ART combinations (OR = 1.79, 95%CI(1.39–2.32)) compared to NRTI+NNRTI combinations; and being hepatitis C co-infected (OR = 1.27, 95%CI(1.06–1.52)). Patients aged >30 years (31–40 years OR = 0.81, 95%CI(0.73–0.89); 41–50 years OR = 0.73, 95%CI(0.64–0.83); and >50 years OR = 0.77, 95%CI(0.64–0.93)); female sex (OR = 0.81, 95%CI(0.72–0.90)); and being from upper middle (OR = 0.78, 95%CI(0.70–0.80)) or high-income countries (OR = 0.42, 95%CI(0.35–0.51)), were less likely to have missed visits. Almost 40% of our patients had a missed clinic visit. Early ART adherence was an indicator of subsequent clinic visits. Intensive counselling and adherence support should be provided at ART initiation in order to optimise long-term clinic attendance and maximise treatment outcomes.